REINFORCING THE TRANSITION FROM EARLY CHILDHOOD EDUCATION TO ELEMENTARY SCHOOL: (A Study of Basic Understanding of Indonesia Through Crossswod Puzzle Games) - Gumilar, Eko Bayu; Ahmad Mukhlasin; Kristina Gita Permatasari; Yeri Utami (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
Transitioning from early childhood education to elementary school constitutes a critical phase in the educational journey of children in Indonesia today. This transition involves acclimating young learners to a substantially different educational environment than their early childhood education. To facilitate a smooth transition, elementary schools must establish robust internal regulations to prepare students for this crucial milestone. This research endeavors to innovate and provide practical strategies to assist prospective elementary school students in their preparation, particularly in the ongoing independent curriculum utilizing the Pancasila student profile strengthening project, commonly referred to as P5. A central aspect of this study involves the integration of Basic Understanding Of Indonesia through crossword Puzzle Games for Early Childhood learners. This initiative aims to introduce educational media that fosters character development and simultaneously offers parents valuable insights into their children's characters as they prepare for the transition from early childhood education to elementary education. The study employs the ADDIE model approach, which encompasses five stages: needs analysis, planning, media production, evaluation, and implementation. Validator questionnaires and data collection methods were employed to assess the effectiveness of the puzzle media. Validation results indicated a percentage of 3.95% for the puzzle media and 3.80% for the puzzle content media. Combining these validation results, the researcher conducted comprehensive testing of the puzzle game media to gauge its suitability for both media quality and content relevance for children. The findings of this study suggest that integrating Basic Understanding Of Indonesia through crossword Puzzle Games for Early Childhood learners can be a valuable asset in preparing children for the transition from early childhood education to elementary school. The puzzle game media, Designed to deepen character values, demonstrated high acceptance among young learners. The positive outcomes of this research highlight the potential of utilizing innovative educational media to enhance character development and facilitate a smoother transition into elementary education for early childhood learners in Indonesia. Further research and implementation may yield additional insights and improvements in this context.